2015
DOI: 10.1145/2746228
|View full text |Cite
|
Sign up to set email alerts
|

On Kinetic Delaunay Triangulations

Abstract: Let P be a collection of n points in the plane, each moving along some straight line at unit speed. We obtain an almost tight upper bound of O(n 2+ε ), for any ε > 0, on the maximum number of discrete changes that the Delaunay triangulation DT(P) of P experiences during this motion. Our analysis is cast in a purely topological setting, where we only assume that (i) any four points can be co-circular at most three times, and (ii) no triple of points can be collinear more than twice; these assumptions hold for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is one of the long outstanding open problems if this bound can be improved [8,9]. Only recently, Rubin [24] showed that if all sites move linearly and with the same speed, the number of changes is at most O(n 2+ε ) for some arbitrarily small ε > 0. For arbitrary speeds, the best known bound is still O(n 3 β 4 (n)).…”
Section: Related Workmentioning
confidence: 99%
“…It is one of the long outstanding open problems if this bound can be improved [8,9]. Only recently, Rubin [24] showed that if all sites move linearly and with the same speed, the number of changes is at most O(n 2+ε ) for some arbitrarily small ε > 0. For arbitrary speeds, the best known bound is still O(n 3 β 4 (n)).…”
Section: Related Workmentioning
confidence: 99%